Quality of ‘Fuji suprema’ apples influenced by long-term annuaaddition of phosphorus to the soil Qualidade de frutos de maçã ‘Fuji suprema’ influenciada pela adição anual de longo prazo de fósforo ao solo - Gerber J.M.* (2018)
© 2018, Universidade Federal de Santa Maria. All rights reserved.Fertilization of apple orchards with phosphorus (P) has received less attention than with nitrogen and potassium. In Brazil, the information about apple response to soil P addition is meager. The objective of this study was to evaluate the long-term effect of annual soil P addition on quality and mineral composition of apple fruits. The experiment started in 2010, in a commercial orchard located in the São Joaquim, Southern of Brazil. The orchard consisted of ´Fuji Suprema’, planted in high-density on a Haplumbrept soil. Treatments consisted of 0, 40, 80, 120 and 160kg ha-1 P2O5 applied annually starting in 2010 broadcast over the soil surface along the tree row. Evaluations were performed from 2012/2013 through 2014/2015 growing seasons. We harvested three samples from each experimental unit. One sample was cold stored in a controlled atmosphere chamber for six months; the others were immediately evaluated for firmness, total soluble solids, titratable acidity (TA), skin color, and the concentrations of N, P, K, Ca and Mg in the fruit flesh. Application of P to the soil affected only flesh firmness at harvest and TA after six months of storage in the 2012/2013 season, as well as firmness after six months of storage in the 2013/2014 season. In the 2014/2015 season, the addition of P reduced fruit color but only at harvest. Addition of P to the soil affected the levels of P in the fruit in the 2012/2013 season, as well as N and the N/Ca ratio of fruit in the 2014/2015 season. Overall, attributes related to fruit quality of cultivar Fuji Suprema were slightly affected by long-term annual addition of P to the soil.